Optimal silkworm larva host for high-level production of Mus musculus IL-4 using a baculovirus expression vector system - Kobayashi, Masahiko; Xu, Jian; Kakino, Kohei; Masuda, Akitsu; Hino, Masato; Fujimoto, Naoki; Minamihata, Kosuke; Kamiya, Noriho; Mon, Hiroaki; Iida, Hiroshi; Takahashi, Masateru; Kusakabe, Takahiro; et al. (Journal of Asia-Pacific entomology, 2020)
[Display omitted] •Recombinant MmIL-4 was expressed and purified by the silkworm-BEVS.•C-tagged rMmIL-4 is a better construct to produce rMmIL-4 in the silkworm-BEVS.•We found that the n70 strain produced the highest amount of rMmIL-4 among 19 silkworm strains. Interleukine-4 (IL-4) is a cytokine that plays an important role in the immune system and recognized as a biological medicine. Therefore, there is a demand for the production of IL-4 with high performance. The expression of a recombinant IL-4 protein in the prokaryotic system usually results in the formation of an inclusion body. To date, the solution to obtain those active products without the refolding process remains to be established. In this study, we tried to acquire a biologically active recombinant Mus musculus IL-4 (rMmIL-4) using a silkworm-baculovirus expression vector system (silkworm-BEVS). We constructed two recombinant baculoviruses coding rMmIL-4 with the distinct location of affinity purification tags and succeeded in the expression and purification of rMmIL-4 proteins directly without the refolding process. Both purified proteins displayed comparable biological activity to the commercial proteins produced by the E. coli expression system. Besides, we performed screening of silkworm strains to seek optimal hosts for the mass-production of rMmIL-4. Intriguingly, we found that some silkworm strains showed significantly higher secretion levels of rMmIL-4 in silkworm sera. Our study provides meaningful insights into the industrial-scale production of rMmIL-4 with high productivity for pharmaceutical applications in the future.